Tumor necrosis factor-alpha regulates photoreceptor cell autophagy after retinal detachment - Xie, Jia (Sci Rep, 2017)
Photoreceptor cell death is the ultimate process underlying many retinal diseases, including retinal detachment (RD). Both autophagy and inflammatory factors, such as tumor necrosis factor-alpha (TNF-α), participate in photoreceptor cell death after RD. In this study, we examined whether TNF-α inhibition would impact the autophagy of photoreceptors and reduce the death of photoreceptors after retinal detachment (RD). RD models were created in C57BL/6J mice by a subretinal injection of 1% hyaluronic acid. The TNF-α inhibitor infliximab was administered via intraperitoneal injection two hours before RD. The levels of TNF-α and the autophagy-related proteins Atg5 and LC3B were assayed by immunofluorescence at 1 day, 3 days, and 7 days following RD. Apoptosis was examined at 3 days post-detachment via TUNEL assays. Photoreceptor cell counts were assessed at 7 days after RD. After RD, the protein levels of LC3B and Atg5 increased and reached a peak at 3 days, which decreased at 7 days. The expression of LC3B and Atg5 was prolonged and increased at a slower rate with TNF-α inhibition. The moderate augmentation and extension of autophagy through TNF-α inhibition resulted in the reduction of apoptosis and the enhancement of photoreceptor cell survival.